Biotinylated Fluorescent Polymeric Nanoparticles for Enhanced Immunostaining. Issue 4 (19th February 2023) - Yudhistira, Tesla; Da Silva, Elisabete Cruz; Combes, Antoine; Lehmann, Maxime; Reisch, Andreas; Klymchenko, Andrey S.
Abstract: The performance of fluorescence immunostaining is physically limited by the brightness of organic dyes, whereas fluorescence labeling with multiple dyes per antibody can lead to dye self‐quenching. The present work reports a methodology of antibody labeling by biotinylated zwitterionic dye‐loaded polymeric nanoparticles (NPs). A rationally designed hydrophobic polymer, poly(ethyl methacrylate) bearing charged, zwitterionic and biotin groups (PEMA‐ZI‐biotin), enables preparation of small (14 nm) and bright fluorescent biotinylated NPs loaded with large quantities of cationic rhodamine dye with bulky hydrophobic counterion (fluorinated tetraphenylborate). The biotin exposure at the particle surface is confirmed by Förster resonance energy transfer with dye‐streptavidin conjugate. Single‐particle microscopy validates specific binding to biotinylated surfaces, with particle brightness 21‐fold higher than quantum dot‐585 (QD‐585) at 550 nm excitation. The nanoimmunostaining method, which couples biotinylated antibody (cetuximab) with bright biotinylated zwitterionic NPs through streptavidin, significantly improves fluorescence imaging of target epidermal growth factor receptors (EGFR) on the cell surface compared to a dye‐based labeling. Importantly, cetuximab labeled with PEMA‐ZI‐biotin NPs can differentiate cells with distinct expression levels of EGFR cancer marker. The developed nanoprobes can greatly amplify the signal from labeled antibodies, and thus become a useful tool in the high‐sensitivity detection of disease biomarkers. Abstract : A nanoimmunostaining method is developed based on bright and small (14 nm) biotinylated zwitterionic nanoparticles built of a rationally designed hydrophobic polymer, poly(ethyl methacrylate) bearing charged, zwitterionic and biotin groups. In combination with biotinylated antibody (cetuximab), it significantly improves fluorescence imaging of target epidermal growth factor receptor on the cell surface compared to a dye‐based labeling.